Academic roots: the most prolific authors of bibliometrics - Ibrahim S.IIP., M.P, Cecep (Jurnal Literasi Perpustakaan dan Informasi: Jurnal Penelitian Kajian Perpustakaan dan Informasi, 2024)
The purpose of this study is to discover the academic roots of the world's most prolific authors of bibliometrics research. José Mara Merigó, Lutz Bormann, Yuhshan Ho, and Giovanni Abramo are bibliometric research professionals in Europe and Asia. The research method employs a bibliometric methodology using reference publication year spectroscopy (RPYS). This study has three stages: data collecting, data processing, and outcome analysis. Data is gathered from the Scopus database by entering the topic "bibliometrics" on Researcher discovery and counting the number of matching documents from 2017 to the present. There are 247 data documents in all. CRExplorer software is also employed in this data processing. To import 247 research documents into the software, the CRExplorer software was utilised, and all import strategies were used. The scholarly roots' discovery results the most prolific authors of bibliometrics research in the world, José Mara Merigó, Lutz Bormann, Yuhshan Ho, and Giovanni Abramo, demonstrated that they used both the straight count and complete count approaches. The most prolific bibliometrics authors cited their own works or self-citation. The four bibliometric research experts ensure that no one is utilised as a role model or ideal in performing bibliometric research.